Institutional design in new democracies: Eastern Europe and Latin America - Lijphart, Arend; Waisman, Carlos Horacio (Latin America in global perspective, 1996)
"Excellent treatment of the problems involved in the institutional design of democratization. Using a comparative perspective, authors examine the relationship between the tasks of institutional design and the policy outcomes of economic and political liberalization in Latin America and in Central and Eastern Europe. Focuses on how institutions serve a market economy, the design of electoral laws, and executive-legislative relations. Although differences do exist, authors find that 'Eastern Europe and Latin America are conceptual and theoretical neighbors rather than distant strangers' to the process of democratization"--Handbook of Latin American Studies, v. 57